2018
DOI: 10.1093/jopart/muy038
|View full text |Cite
|
Sign up to set email alerts
|

Equal Access to the Top? Representative Bureaucracy and Politicians’ Recruitment Preferences for Top Administrative Staff

Abstract: Although a voluminous literature on representative bureaucracy and minority discrimination suggests that characteristics other than qualifications influence hiring decisions, little is known about whether this also pertains to the top positions in political-administrative organizations. To shed light on this question, we ask how candidate ethnicity, gender, and age affect the recruitment preferences among politicians regarding the candidates for top administrative positions. Our study uses a survey experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 81 publications
2
24
0
5
Order By: Relevance
“…Second, using two different survey experimental designs in Studies 2 and 3, we found no and positive discrimination, respectively. While these conclusions are both theoretically and empirically improbable, they resemble those found in a recent survey experiment on hiring discrimination by Baekgaard and George (). Baekgaard and George () use a design that is in many ways similar to our Study 3: Both experiments were performed in February 2017 using an online survey sent to public sector staff, consider the hiring for administrative public sector positions and use similar names to represent ethnic majorities (e.g.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Second, using two different survey experimental designs in Studies 2 and 3, we found no and positive discrimination, respectively. While these conclusions are both theoretically and empirically improbable, they resemble those found in a recent survey experiment on hiring discrimination by Baekgaard and George (). Baekgaard and George () use a design that is in many ways similar to our Study 3: Both experiments were performed in February 2017 using an online survey sent to public sector staff, consider the hiring for administrative public sector positions and use similar names to represent ethnic majorities (e.g.…”
Section: Discussionsupporting
confidence: 73%
“…This procedure estimates that it is 10 times more likely than not that the effects from the two studies are the same (BF = 10.13). While Study 3 is by no means an exact replication of Baekgaard and George (), this comparison certainly suggests that our survey experiments are representative of studies being conducted in this field of research – not only in terms of design, but also in terms of the obtained results.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Second, and relatedly, as argued by Riccucci and Van Ryzin (), studies of representative bureaucracy associate minority representation with more equal outcomes through a more inclusive work climate (Andrews and Ashworth ), less misconduct by street‐level bureaucrats (Hong ), higher willingness to coproduce (Riccucci, Van Ryzin, and Li ), and, in general, better citizen outcomes (Guul ). Finally, while there are relatively few studies of employment discrimination in the public sector (Leasher and Miller ), some recent studies indicate that ethnic minorities are also at a disadvantage when applying for jobs in the public sector (Carlsson and Rooth ; Villadsen and Wulff ; but see also Baekgaard and George ).…”
mentioning
confidence: 99%